Cold spell en route delays spring arrival and decreases apparent survival in a long-distance migratory songbird - Briedis, Martins (BMC Ecol, 2017)
BACKGROUND: Adjusting the timing of annual events to gradual changes in environmental conditions is necessary for population viability. However, adaptations to weather extremes are poorly documented in migratory species. Due to their vast seasonal movements, long-distance migrants face unique challenges in responding to changes as they rely on an endogenous circannual rhythm to cue the timing of their migration. Furthermore, the exact mechanisms that explain how environmental factors shape the migration schedules of long-distance migrants are often unknown. RESULTS: Here we show that long-distance migrating semi-collared flycatchers Ficedula semitorquata delayed the last phase of their spring migration and the population suffered low return rates to breeding sites while enduring a severe cold spell en route. We found that the onset of spring migration in Africa and the timing of Sahara crossing were consistent between early and late springs while the arrival at the breeding site depended on spring phenology at stopover areas in each particular year. CONCLUSION: Understanding how environmental stimuli and endogenous circannual rhythms interact can improve predictions of the consequences of climate changes on migratory animals. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12898-017-0121-4) contains supplementary material, which is available to authorized users.